Rotulagem de alimentos: atualização das novas diretrizes para alimentos - Alves, Beatriz da Rocha (2023)
This study is a systematic literature review of food legislation, with the objective of identifying the main changes in nutritional labeling guidelines for packaged foods and assessing their impact on food product labels. 25 articles were found in scientific journals and books related to the theme, of which 16 were selected and used in the research. The guiding question was "What are the main changes in nutrition labeling guidelines for packaged foods and how do they affect food product labels?". Limiting factors included the time available for the literature review, the language of the articles and the approach used in selecting the studies. As a result, the new food labeling legislation seeks to provide clear and complete information to consumers, including nutritional table and front labeling. The initiative aims to promote more informed and healthy choices, contributing to the prevention of chronic diseases. Industry must comply with regulations to ensure transparency in consumer information. The study concludes that the adoption of new regulations by the food industry will allow consumers to correctly understand the nutritional information on food product labels.